2008
DOI: 10.1016/j.seizure.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system adverse effects of new antiepileptic drugs

Abstract: No comparison between drugs was possible. One CNS AE was significantly more frequent for levetiracetam, two for zonisamide and gabapentin, three for lamotrigine and four for pregabalin and topiramate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…OXC may cause hyponatremia more often than CBZ. Levetiracetam (LEV), which has a better tolerability profile (34), share many of the advantages offered by LTG and GBP, although these drugs have not yet been assessed in this population of patients.…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…OXC may cause hyponatremia more often than CBZ. Levetiracetam (LEV), which has a better tolerability profile (34), share many of the advantages offered by LTG and GBP, although these drugs have not yet been assessed in this population of patients.…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…[21][22][23] A meta-analysis by Zaccara and colleagues compared the central nervous system effects of various new antiepileptic drugs from randomized double-blind trials and found that levetiracetam was significantly associated with somnolence. 66 Although this meta-analysis did not find a relationship between somnolence and drug dose, other clinical trials have seen a dose response relationship. 21 Bootsma and colleagues have reported that somnolence or tiredness appeared to be more common in patients without mental handicap compared to those with mental handicaps.…”
Section: Safety Tolerability and Adverse Effectsmentioning
confidence: 60%
“…This is typically done proactively rather than in response to a specific problem. For example, many AEDs contribute to dizziness, sedation, fatigue, and inattention [16]. Additionally, some of the older AEDs (such as phenytoin and valproate) affect hepatic enzyme metabolism which is particularly undesirable for patients taking multiple medications.…”
Section: Discussionmentioning
confidence: 99%
“…After successful seizure control, AED polypharmacy may lead to adverse side effects, drug-drug interactions between AEDs and non-AEDs, and excessive cost for patients after hospital discharge if their polypharmacy regimen is continued. Common AED side effects include dizziness, fatigue, nausea and cognitive dysfunction [16]. AED weaning after successful seizure control may avoid or minimize these complications.…”
Section: Introductionmentioning
confidence: 99%